Interdisciplinary Diagnostic Complex for Assessing the Mastery of Educational Programs by Senior Preschool Children - G.V. Molchanova; A.G. Gogoberidze; R.I. Yafizova (Moscow State University of Psychology and Education, 2024)
The article presents the results of a population study on the mental and physical development of preschool children using a standardized interdisciplinary diagnostic complex (State Registration Number 624012303596-7 dated January 23, 2024). The study involved 203 children from different regions of the Russian Federation: 100 girls (49,3%) and 103 boys (50,7%). The median age was 69 months (5 years and 9 months). There was no significant age difference between girls and boys (t(80)=1,87; p=0,07). New research data, demonstrating the results of six-year-old children based on the interdisciplinary complex of psychological and pedagogical diagnostics developed by the authors, identify the potential and risks of child development, forecast and highlight possible difficulties in mastering the educational program in accordance with the targeted benchmarks of the Federal State Educational Standard for Preschool Education and the planned outcomes of the Federal Preschool Education Program. The results obtained allow for the prediction of the success in mastering the educational program by six-year-old children in relation to the planned outcomes of the FPEP, based on the formation of certain systemic qualities of the child's personality.